The Effect of the STAD Model Supported by House Game Animal on Elementary School Students' Learning Interest - Latifah, Nurul; Malihatul Hawa, Anni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to determine the effect of using the STAD learning model supported by the House Game Animal on students' learning interest. The sampling technique used is purposive sampling. The data collection techniques used are questionnaires, observation, structured interviews, and documentation. The data analysis techniques used are validity, reliability, difficulty level, distinguishing power, normality, homogeneity, and hypothesis tests consisting of independent sample t-tests and simple linear regression tests. The research results reveal that (1) there is a significant difference in students' learning interest in the STAD learning model supported by the House Game Animal. This is proven by the calculated sig value of 0.003 < 0.05, which indicates rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). (2) Using the STAD learning model through the House Game Animal significantly influenced students' interest in learning. This is proven by the obtained significance value of 0.000 < 0.005 and the tcount value of 8,269 > ttable 2.069. As a result, House Game Animal-supported the STAD learning model has significant differences and influence in increasing students' learning interest.